Hybridization and anisotropy in the exchange interaction in three-dimensional Dirac semimetals - Mastrogiuseppe, Diego Martín (2016)
We study the Ruderman-Kittel-Kasuya-Yosida interaction in three-dimensional Dirac semimetals. Using retarded Green's functions in real space, we obtain and analyze asymptotic expressions for the interaction, with magnetic impurities at different distances and relative angle with respect to high symmetry directions on the lattice. We show that the Fermi velocity anisotropy in these materials produces a strong renormalization of the magnitude of the interaction, as well as a correction to the frequency of oscillation in real space. Hybridization of the impurities to different conduction electron orbitals are shown to result in interesting anisotropic spin-spin interactions which can generate spiral spin structures in doped samples.